2013
DOI: 10.1039/c2an36192b
|View full text |Cite
|
Sign up to set email alerts
|

Tackling reproducibility in microcantilever biosensors: a statistical approach for sensitive and specific end-point detection of immunoreactions

Abstract: aIn the biomedical field, end-point detection bioassays such as enzyme-linked immunosorbent assays (ELISAs) are essential tools because of their simplicity, high-throughput, and suitability for their use at the point-of-care. End-point bioassays are significantly constrained by the need of sample labeling with fluorescent or colorimetric tags for subsequent detection. A promising strategy to overcome these limitations is to harness recent advances in label-free biological nanosensors. Here we analyse the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…antibodies and detection antibodies, respectively, using a procedure that ensures optimal recognition efficiency and ultralow fouling capability 10 . The materials and methods used in the functionalization and sandwich assays are detailed in Supplementary Section 1.…”
Section: The Sandwich Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…antibodies and detection antibodies, respectively, using a procedure that ensures optimal recognition efficiency and ultralow fouling capability 10 . The materials and methods used in the functionalization and sandwich assays are detailed in Supplementary Section 1.…”
Section: The Sandwich Assaymentioning
confidence: 99%
“…Nanotechnology provides biosensors with unprecedented levels of sensitivity that can be used to monitor biomarkers predicted by proteomics. However, such nanosensors have significant issues regarding specificity and reproducibility, and are thus not yet ready for biomarker screening in blood [8][9][10] . These problems occur, in part, because of the extreme difficulty in detecting low-abundance protein biomarkers among plasma proteins, which can have concentrations that are around seven orders of magnitude higher (albumins, for example, have concentrations of ∼40 mg ml −1 ).…”
mentioning
confidence: 98%
“…However, their application to clinical diagnosis will also demand for a method capable of providing hundreds of measurements in a short time, as well as manageable preparation steps for the microcantilever sensors that can still provide reproducible mechanical patterns. 9,10 All the above reasons highlight the need to pursue in depth understanding of the hybridization process and of the conformations of the DNA layers.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recent theoretical and experimental work has highlighted the fact that even slightly different experimental conditions, such as ionic strength, temperature or pH variations during immobilization, may lead to largely divergent mechanical effects. 17,18 The final strand density in self-assembled monolayers plays a critical role in nanomechanical sensing 9 and it is indeed far from being fully controllable. 19,[20][21][22][23] One singularly limiting difficulty has been to accomplish the anchoring of the ssDNA probes with a well-defined uniform density and a standing up conformation.…”
Section: Introductionmentioning
confidence: 99%
“…PEG is a protein-resistant and anti-fouling polymer with low toxicity and high biocompatibility [58]. Studies on cantilevers with both BSA and PEG layers revealed that PEG is more successful in depression of nonspecific binding [83,237]. Yen et al [238] recently demonstrated the application of ethanolamine as the blocking agent in the detection of C-reactive protein (CRP).…”
Section: Hybrid Sensing Devicesmentioning
confidence: 99%